Co‐occurrence of Jalili syndrome and muscular overgrowth. Issue 8 (6th June 2017) - Wawrocka, Anna; Walczak‐Sztulpa, Joanna; Badura‐Stronka, Magdalena; Owecki, Michal; Kopczynski, Przemysław; Mrukwa‐Kominek, Ewa; Skorczyk‐Werner, Anna; Gasperowicz, Piotr; Ploski, Rafal; Krawczynski, Maciej R.
Abstract : Jalili syndrome is a rare disorder inherited in an autosomal recessive pattern manifesting as a combination of cone‐rod dystrophy including progressive loss of visual acuity, color blindness, photophobia, and amelogenesis imperfecta with hypoplastic, immature, or hypocalcified dental enamel. It is caused by mutations in CNNM4, which encodes the ancient conserved domain protein 4. Here we report three brothers with Jalili syndrome and muscle overgrowth of the legs. Myopathic changes were found in needle electromyography. Mutational analysis showed in all three brothers a novel likely pathogenic homozygous missense substitution in exon 1 (c.1076T>C, p.(Leu359Pro)) of CNNM4 . Both parents were carriers for the variant. In order to exclude other causative variants that could modify the patients' phenotype we performed exome sequencing and MLPA analysis of the DMD gene in Patient 1. These analyses did not identify any additional variants. Our results expand the mutational spectrum associated with Jalili syndrome and suggest that mild myopathy with muscle overgrowth of the legs could be a newly identified manifestation of the disorder.